(untitled) (Bangladesh Journal of Medical Science, 2014)
Introduction: Anemia is a common complication of ESRD with different etiologies. The most common cause of anemia in such patients is insufficient production of erythropoietin by kidneys. Another possible reason is copper deficiency, thus, this study is aimed to evaluate the serum copper level among hemodialysis patients with and without anemia and to compare them to healthy controls. Material and Methods: A total number of 56 patients who underwent regular hemodialysis due to their ESRD were enrolled and divided into two groups of 28 according to their Hgb results including patients with anemia (Hgb<11 gr/dl) and patients without anemia (Hgb>11 gr/dl). Also, 28 healthy individuals participated as the control group. Venous blood samples were collected from patients prior to hemodialysis. Spectrophotometry employed for copper measurements. Data were analyzed using t-test and Pearson regression analysis. Results: Mean age of patients was 44.36±15.80 years. No significant difference was present among the three groups with regarding to age and gender. Mean and SD of serum copper in patients with anemia, without anemia, and controls were 180.11±54.48, 139.66±35.57 and 155.82±42.06 µg/dl respectively. Serum copper level was significantly higher in hemodialysis patients with anemia compared with those without anemia (p<0.03). Also a significant inverse regression between serum copper and Hgb was present in all hemodialysis patients (p=0.02, r=-0.37). Conclusion: Higher levels of serum copper in anemic patients could be a result of restraining role of high serum copper on iron absorption that has a negative effect on the production of Hgb. However, complementary studies are required. DOI: http://dx.doi.org/10.3329/bjms.v14i1.16853 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.43-48